O discurso do profissional de ginástica em academia no Rio de Janeiro - Carlos Alberto de Andrade Coelho Filho (Universidade Federal do Rio Grande do Sul, 2000)
This study belongs to the line of research on the Social Representation of the physical education' actors. It has for analysis object the meaning of the gymnastics professionals' speech in great academies in the City of Rio de Janeiro on its work process and about the representations that accompany it. The theoretical reference comes from the "analysis of the speech", of French background, of ¡nterdiscipline motivation, based on Bakhtin, Foucault, Pêcheux and Maingueneau.